(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The aim of the present study was to investigate the effect of oral melatonin administration on foetal growth retardation, utero-placental antioxidant enzymes activities and lipid peroxidation in experimental diabetic rats. Twenty pregnant rats were divided into four groups of five rats each. Diabetes mellitus was induced by a single intraperitoneal administration of 120mg/kg body weight of alloxan. From gestational day 5 to 19, 5mg/kg and 10mg/kg of oral melatonin were administered to the rats with clearly manifested gestational diabetes. On the 19th day of gestation, the rats were sacrificed by cervical dislocation and placental, foetal and uterine tissues were harvested for estimation of tissue glutathione peroxidase (GPx) activity and malondialdehyde (MDA) levels. Foetal weight, foetal size, placental and plasma glucose were also determined. Results showed that, in diabetic rats, foetal growth retardation was associated with a significant reduction in placental and uterine antioxidant enzymes (GPx) activities (P<0.001) and increased lipid peroxidation as evidenced by raised MDA concentration (P< 0.05). Treatment with oral melatonin significantly improved the foetal weight, placental and uterine antioxidant enzymes activities as well as reduced lipid peroxidation, without affecting the degree of hyperglycaemia. Effects of melatonin on foetal growth are presumed to be dependent on its ability to improve uteroplacental antioxidant enzymes activities and reduce lipid peroxidation. Bangladesh Pharmaceutical Journal 18(1): 42-47, 2015